Revision of the camel spider genus Eremocosta Roewer and a description of the female Eremocosta gigas Roewer (Arachnida, Solifugae) - Cushing, Paula E.; Channiago, Felix; Brookhart, Jack O. (Zootaxa, 2018)
A recent phylogenetic analysis demonstrated that the solifuge genus Eremocosta (Eremobatidae), although not monophyletic, formed a strongly supported group, rendered paraphyletic by the exclusion of E. acuitlapanensis, which we herein determine is misplaced in this genus. We revise the taxonomy of the genus Eremocosta. Nine species of the 13 currently placed in the genus are retained, E. bajaensis (Muma 1986), E. calexicensis (Muma 1951), E. formidabilus (Simon 1879), E. gigas Roewer 1934, E. gigasella (Muma 1970), E. spinipalpis (Kraepelin 1899), E. striata (Putnam 1883), and E. titania (Muma 1951). Eremocosta fusca (Muma 1986) and E. montezuma (Roewer 1934) are returned to the genus Eremorhax along with E. arenarum. Eremocosta hystrix and Eremocosta acuitlapanensis (Vázquez & Gaviño-Rojas 2000) are transferred to Eremobates. We re-evaluated E. nigrimana (Pocock 1895) and determined that, since the type shows the ventrodistal concavity (VDC) diagnostic for the genus Eremocosta, it should be retained in that genus; however, because the type locality is identified as Afghanistan, far outside the range of any Eremobatidae, its status and placement remain uncertain. Eremocosta robusta (Roewer 1934) was designated nomen dubium by Muma and we maintain this designation. We provide a key to the species of Eremocosta and provide a description of the female of E. gigas.